1989
DOI: 10.1902/jop.1989.60.8.467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Penicillin and Erythromycin on the Clinical Parameters of the Periodontium

Abstract: The clinical effects of systemic penicillin and erythromycin on the periodontium were investigated. There are only a few studies of the effects of these antibiotics on clinical periodontal parameters. Of the 72 subjects in the study, 24 belonged to the penicillin group, 21 to the erythromycin group and 27 to the control group. Plaque and gingival indices, tooth mobility, and probing depths of gingival pockets were recorded before the drug treatment. Radiographs were taken. Both antibiotics decreased plaque, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 7 publications
0
30
0
2
Order By: Relevance
“…There is scarce information available on the microflora of gingival abscesses, or other type of abscesses with other distinct etiology. The exception may be the studies of the microflora of abscesses related with systemic antibiotic intake in periodontitis patients, without mechanical treatment (Helovuo & Paunio 1989, Helovuo et al 1993, Topoll et al 1990. In this type of periodontal abscesses, besides an occurrence of periodontal pathogens similar to other abscesses in periodontitis (Topoll et al 1990), opportunistic bacteria were detected, and Staphylococcus aureus was found in abscesses of patients with previous penicillin intake.…”
Section: Microbiologymentioning
confidence: 98%
See 2 more Smart Citations
“…There is scarce information available on the microflora of gingival abscesses, or other type of abscesses with other distinct etiology. The exception may be the studies of the microflora of abscesses related with systemic antibiotic intake in periodontitis patients, without mechanical treatment (Helovuo & Paunio 1989, Helovuo et al 1993, Topoll et al 1990. In this type of periodontal abscesses, besides an occurrence of periodontal pathogens similar to other abscesses in periodontitis (Topoll et al 1990), opportunistic bacteria were detected, and Staphylococcus aureus was found in abscesses of patients with previous penicillin intake.…”
Section: Microbiologymentioning
confidence: 98%
“…Treatment with systemic antibiotics without subgingival debridement in patients with advanced periodontitis may also cause abscess formation (Helovuo & Paunio 1989, Helovuo et al 1993, Topoll et al 1990). Topoll et al (1990) reported on the development of multiple abscesses (from 4 to 12) in 10 untreated periodontal patients, who received systemic antibiotic therapy (penicillin, tetracycline or megacillin) for non-oral infections.…”
Section: Periodontal Abscesses In Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable success of penicillin in treating bacterial infections quickly stimulated a great deal of scientific effort towards the search for other antibiotics. A few studies have evaluated the effect of amoxicillin alone on the microbiological and clinical parameters of periodontal disease (Helovuo & Paunio 1989, Helovuo et al 1993, Abu-Fanas et al 1991a, Hull et al 1989). Metronidazole and amoxicillin, a semisynthetic penicillin, have been used for the treatment of advanced periodontitis.…”
mentioning
confidence: 99%
“…[70] Thus, administration of beta-lactamase sensitive penicillins is not generally recommended and in some cases, may accelerate periodontal destruction. [7172] The mechanism can be circumvented by the use of a β- lactamase inhibitor such as clavulanic acid, and this is used in the combination of amoxycillin with clavulanic acid in Augmentin. Augmentin is available as 375 mg or 625 mg, tablet which contain 250 mg and 500 mg of amoxicillin, respectively, and 125 mg clavulanic acid (Same amount of clavulanic acid is present in 375 mg and 625 mg tablets).…”
Section: Introductionmentioning
confidence: 99%